El principio de igualdad formal y material y su aplicación en los procesos de cotización de obra. - Duche Delgado, Katherine Alexandra (2023)
This research work will study the effect, application and scope of the principle of equality in its two dimensions in the work quotation processes of the National Public Procurement System. There are several questions that compose this type of processes due to the requirements established in the pre-contractual stage; they contain equal opportunities considering that there are additional scores in certain cases. Therefore, the main objective of this project is based on establishing whether this principle is applied in these processes. Therefore, it is intended to analyze how this principle is applied in pre-contractual procedures, and to identify how it is handled by adding the preference score in favor of actors of popular and solidarity economy; that is, if it makes these procedures inclusive or exclusive. This project was carried out using the following methods: legal doctrinal, legal analytical, inductive and descriptive.